Notary Authority Based on Article 15 Paragraph (2) Letter F of Notary Position Act - Wiharja, I Wayan Tri Wira; Amiruddin,; Sahnan, (International Journal of Scientific Research and Management (IJSRM), 2019)
Notaries have a very important role in legal traffic, especially in the field of civil law, because a notary is domiciled as a public official who has the authority to make other deeds and authorities. One of the authorities granted is to make a deed relating to land, as referred to in Article 15 paragraph (2) letter F of the Notary Position Act.This research shows the authority of the notary in making land deeds in a narrow sense, namely the Power of Attorney Charges Mortgage (SKMHT) and in the broad sense namely the Roya Concert Act, the Right of Release Deed, the Declaration of inheritance rights for Indonesian citizens of the Chinese group. The power of attorney to impose liability the juridical implication is a power of attorney that cannot be withdrawn and does not end by any reason except with the making of the deed of rights to give the dependent. The deed of Roya concentration has a position as a substitute certificate of liability in the write-off of mortgage rights and has no executive power. With respect to the rights release deed, the juridical implications lead to the release of land rights from holders of ownership rights to individual land to the rights applicant, namely a private legal entity, first released to the state accompanied by compensation. Regarding the certificate of inheritance rights made by a notary for Indonesian citizens of Chinese descent the juridical implication is the basis for determining rights as heirs in the transfer of rights on the basis of inheritance.